To bleed or not to bleed? Case series and discussion of haemorrhage risk with enzymatic debridement in burn injuries - Saiidy Hasham; Harjoat Riyat; Anthony Fletcher; Ciaran P O'Boyle; Skaria Alexander (SAGE Publishing, 2023)
Introduction Surgical burn excision (along with skin grafting) carries the risk of blood loss. The use of enzymatic debridement agents such as Nexobrid® has gained increased popularity as an alternative to surgical debridement in the management of burns with its reported benefits of selective burn debridement, minimising blood loss and potentially reducing the need for skin grafting. However, there is limited evidence regarding its effects on bleeding. Currently, the manufacturer declares there is no evidence for increased risk of localised bleeding and its systemic effects upon coagulation are less clear. Methods We present two clinical cases demonstrating the possible effects of Nexobrid® on coagulation and bleeding at the debridement site. Comparisons are drawn with the manufacturers' guidance as well as evaluating the current recommendations of its use. Discussion Nexobrid® is a novel therapy and there are few adverse effects reported in the literature. The basis of its appeal is the reduced blood loss at the debridement site and the selectivity it possesses in preserving healthy dermis. However, our cases have demonstrated that haemorrhage can occur and that those using Nexobrid® should be mindful of the potential bleeding risk from varicosities within the burn wound. We have also illustrated that Nexobrid® can be used in patients with pre-existing clotting disorders without requiring the use of blood products. However, we emphasise the importance of haematological support for its safe administration. Lay Summary Nexobrid®, a debriding agent that contains enzymes, has been developed as an alternative to surgery which for most surgeons is the traditional method of removing dead tissue following a burn injury. The active agent is bromelain and this is derived from the stems of pineapples. This novel treatment is increasingly being used in the management of middle to deep skin thickness burns and it seems to have a number of benefits such as reducing blood loss, reducing the need for skin grafting as well as being able to treat burns in certain areas of the body that would be technically challenging to remove in the standard fashion. It simply targets the dead tissue leaving viable remnants of the skin that would hopefully allow healing to occur without the need for surgical intervention. Being a relatively new concept, current evidence regarding the safety and value of Nexobrid® continues to develop. In 2020, an agreement guideline outlining best practice with the use of Nexobrid® was published. In this statement, it was advised that caution should be taken when using Nexobrid® in patients who have blood clotting disturbances as this could increase the likelihood of bleeding. However, they did not mention that excessive bleeding can potentially occur with this treatment. We present two clinical cases demonstrating the possible effects of Nexobrid® on the clotting system and bleeding at the application site. Comparisons are drawn with the manufacturers' guidance as well as assessing the current recommendations of its use. We illustrate that Nexobrid® can be safely used in patients with pre-existing clotting disturbances if the correct procedures are performed. We also highlight the potential complication of excessive bleeding if Nexobrid® is used in patients who have co-existing enlarged surface veins along with their burn injury. We feel the guidance should be updated to reflect these findings.